Low-energy electron emission in the strong-field Ionization of rare gas clusters - Schütte, Bernd; Peltz, Christian; Austin, Dane R.; Strüber, Christian; Ye, Peng; Rouzée, Arnaud; Vrakking, Marc J. J.; Golubev, Nikolay V.; Kuleff, Alexander I.; Fennel, Thomas; Marangos, Jon P. (Physical review letters, 2018)
Clusters and nanoparticles have been widely investigated to determine how plasmonic near fields influence the strong-field induced energetic electron emission from finite systems. We focus on the contrary, i.e., the slow electrons, and discuss a hitherto unidentified low-energy structure (LES) in the photoemission spectra of rare gas clusters in intense near-infrared laser pulses. For Ar and Kr clusters we find, besides field-driven fast electrons, a robust and nearly isotropic emission of electrons with <4 eV kinetic energies that dominates the total yield. Molecular dynamics simulations reveal a correlated few-body decay process involving quasifree electrons and multiply excited ions in the nonequilibrium nanoplasma that results in a dominant LES feature. Our results indicate that the LES emission occurs after significant nanoplasma expansion, and that it is a generic phenomenon in intense laser nanoparticle interactions, which is likely to influence the formation of highly charged ions.
Gesehen am 02.09.2019